Effectiveness Of Socialization Of Immunization Of Pentavalen Continued By Health Persons To Mothers Compliance Batita In Working Center Health Center Community Beji Malang, East Java - Sutikno, Agus; Haida, Ana Ifa Nurul; Sari, Dian Yovita (STIKes Surya Mitra Husada, 2018)
Background: Pentavalent vaccine has several types of diseases, namely diphtheria, pertussis, tetanus, hepatitis B, inflammation of the brain and pneumonia. However.Forhalalisasi socialization and provision of immunization pentavalen. Purpose : This study aims to find out how the effectiveness of socialization pentavalen immunization by health workers to toddlers in the  working area Beji Puskesmas Kota Batu. Methods : This research was analytic observational with cross sectional approach (one group pre test - post test design) was done to Mrs. Batita in working area BejiPuskesmas Town of Batu in May to June 2017. Respondents were selected in total sampling and conducted questionnaire by using observation sheet before and after further Pentavalen immunization socialization for measurement of Batita mother in immunization implementation. Data collection using using pre-post observation sheet and the result in analysis by using Paired Sample T-test, the significant level used is 95% with value Î± 0, 05. Result : The result of the research shows that before the implementation of Pentavalen Socialization on 17 batitae 17 respondents (30,9%) and the last socialization of Pentavalen to IbuBatita as many as 45 respondents (81,8%), there is significant correlation between effectivity of pentavalent immunization socialization by health worker against Batita housewife in working area Beji Puskesmas Kota Batu p value = 0.000 and Î± = 0,05. Conclusion : In this study the implementation of immunization socialization. IbuBatita will increase awareness and awareness of IbuBatita to immunize her baby in Posyandu or other health services that serve immunization